Drama Excerpt: Tool in Enhancing Speaking Ability for Junior High School - Otan Hidayat; Sigit Apriyanto (IJECA (International Journal of Education and Curriculum Application), 2019)
The study aims to analyze drama excerpts as a tool in teaching speaking for Junior High School at the University of Saint Anthony. It also aims to determine the following: 1. Speaking ability, of the students before exposure on drama excerpt 2. The speaking ability after exposure on drama excerpt 3. The observed improvement among students along with body language, eye contact, introduction and closure, pacing, poise, and voice. 4. Develop Oral communication guide for effective speaking material based on the findings of the study. A descriptive survey is used as a method of this study. The study population consisted of 10 students from 7th-grade students at Saint Anthony University in the Philippines. Based from the findings of the study, found that the respondents were able to perform the conversation in the drama excerpt (because English is the medium of instruction in the Philippines, the result is higher, due to the interventions of a treatment given by the subject teacher on the correct and proper way of delivery and dialogue on drama excerpt, and there is a significant improvement observed to the students after the exposure to drama excerpt.